G20 action on the digital economy: Addressing market failures to improve the health of the digital infrastructure - Paul Twomey (Kiel Institute for the World Economy (IfW), 2017)
Market failures are resulting in network operators and device manufacturers not being incentivized to ensure improved cyber security practices in their operations. The result is a large global base of vulnerable computers, modems/routers and Internet of Things devices which can be manipulated by Cyber criminals. Practical recommendations are made as to how governments could address these market failures (with low-cost to government) and significantly improve the health of the cyber ecosystem.
Keywords: L1; L2; 330; market failures; Internet of Things; internet service providers; cyber security